ANALYSIS OF MODERN REMOTE CONTROL PROTOCOLS AND PROSPECTS FOR THE APPLICATION OF FACTORIAL CODING - LAVDANSKYI, ARTEM; KOROBEINYK, YURII; LAVDANSKA, OLHA; HRESKO, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents an analytical review of modern control protocols for remote unmanned systems, which are actively applied in various fields of activity — from aviation, industrial production, and agriculture to defense, logistics, rescue operations, and environmental monitoring. The study examines the key technical characteristics, advantages, and limitations of the most widely used protocols, including AFHDS, DSMX, Futaba FHSS systems, FASST/FASSTest, ACCST/ACCESS, TBS Crossfire, and others. A comparative analysis of their capabilities is provided in the context of ensuring reliable command transmission, interference resistance, telemetry support, communication range, and responsiveness to changing operational conditions. Special attention is given to the requirements for modern protocols that can guarantee stable and secure control channels under conditions of increased electromagnetic interference, limited bandwidth, and risks of external intervention. The paper highlights the problems that remain relevant, including signal delay, energy consumption of communication modules, integration with autonomous navigation systems, and information security at the levels of data encryption and user authentication. The prospects for protocol development are also considered, with emphasis on the use of 5G technologies, satellite communication channels, and new methods of interference-resistant coding. The importance of protocol standardization is underlined to ensure compatibility between equipment from different manufacturers and to create a unified information space for controlling unmanned systems. In conclusion, the essential characteristics of a reliable control protocol are defined: high interference resistance, low latency, extended telemetry, configuration flexibility, and scalability in complex multichannel systems.